Detection of invasive pulmonary aspergillosis in critically ill patients by combined use of conventional culture, galactomannan, 1-3-beta-D-glucan and Aspergillus specific nested polymerase chain reaction in a prospective pilot study - Boch, Tobias; Reinwald, Mark; Spiess, Birgit; Liebregts, Tobias; Schellongowski, P.; Meybohm, Patrick; Rath, Peter-Michael; Steinmann, Jörg; Trinkmann, Frederik; Britsch, Simone; Michels-Zetsche, Julia D.; Jabbour, Claude; et al. (Journal of critical care, 2018)
Invasive pulmonary aspergillosis (IPA) is an emerging and life-threatening infectious disease in patients admitted to the intensive care unit (ICU). Most diagnostic studies are conducted in hematological patients and results cannot readily be transferred to ICU patients lacking classical host factors. In a multicenter, prospective clinical trial including 44 ICU patients, hematological (n=14) and non-hematological patients (n=30), concurrent serum and bronchoalveolar lavage (BAL) samples were analyzed by conventional culture, galactomannan (GM), 1-3-beta-D-glucan (BDG) as well as an Aspergillus specific nested polymerase chain reaction (PCR). Nine patients (20%) had putative IPA according to AspICU classification. GM and PCR showed superior performance in BAL with sensitivity/specificity of 56%/94% and 44%/94% compared to 33%/97% and 11%/94% in serum. Despite better sensitivity of 89%, BDG showed poor specificity of only 31% (BAL) and 26% (serum). Combination of GM and PCR (BAL) with BDG (serum) resulted in 100% sensitivity, but also reduced specificity to 23%. Whereas mean GM levels were significantly higher in hematological patients BDG and PCR did not differ between hematological and non-hematological patients. Under present clinical conditions test combinations integrating both BAL and blood samples are advantageous. BDG might best serve as possible indicator for ruling out IPA. - Trial registration - ClinicalTrials.gov Identifier: NCT01695499. First posted: September 28, 2012, last update posted: May 8, 2017.
Gesehen am 21.02.2020